PRAKTIK MIXING CODE ARAB – INGGRIS DALAM LAGU (CALL HER RIGHT NOW) OLEH BAYOU: KAJIAN ANTROPOLINGUISTIK - Nursukma Suri; Muhammad Ikram; Alwi Shihab (LP2M UIN Abdul Muthalib Sangadji Ambon, 2025)
This study aims to analyze the patterns and functions of Arabic–English code-mixing in Bayou’s song “Call Her Right Now” and to examine its social meanings using Michael Silverstein’s framework of indexical order. The research employs a qualitative approach, drawing on a literature review and textual analysis of the lyrics. The primary data consist of a lyric transcript verified against the audio recording, annotated for types of switching (e.g., insertion, alternation), and analyzed descriptively and interpretively based on principles of indexicality. The results show that the verses are mostly in English, which gives them a cosmopolitan style and serves narrative purposes. The chorus and post-chorus, on the other hand, are mostly in Arabic, which gives them emotional power and shows that they are authentic to the area. The inserted English phrase “call her right now” functions as a cohesive bridge and a marker of prestige. This study contributes by linking micro-linguistic findings on code-mixing in Arabic popular music to indexical order theory, thereby clarifying how linguistic elements construct hybrid identities. Further research is recommended using multimodal and ethnographic approaches (e.g., listener interviews, music video analysis, or corpus-based studies) to empirically test social reception and language-ideological dynamics